San Rossore 1938: Università degli Studi di Pisa - ARX architetti > Heliopolis 21 (AND Rivista di architetture, città e architetti, 2020)
The project for the new educational centre in the ex-Guidotti area takes its cue from the city context in which it is located. It is articulated in three bodies that vary their height in order to approach the ancient city and its articulation, denouncing to the outside the uses of the internal environments.